THE GENESIS OF QUENTIN SKINNER’S CONTEXTUALIST METHODOLOGY - Hrubiznyi, Stanislav (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2026)
Background. This study is devoted to an analysis of Quentin Skinner’s early methodology, in particular its foundational principles, intellectual sources, and ways of responding to criticism. The main focus is on determining how consistent Skinner’s contextualist methodology remained over the years and whether it underwent any significant changes under the pressure of scholarly polemics. Methods. The study is based on a methodology in the history of philosophy, textual and comparative analysis of Quentin Skinner’s early works, as well as his responses to criticism. It employs a reconstruction of the key concepts of his contextualist methodology and traces their functioning within his polemics with opponents. Results. It has been established that the methodological foundation of Skinner’s contextualism was formed in the works published between 1966 and 1972. This foundation rests on the rejection of "perennial" problems, the requirement to interpret texts through their historical and linguistic context, and the clarification of the illocutionary force of utterances as well as authorial intentions. It is shown that in his later writings Skinner does not abandon these principles, but rather refines, specifies, and defends them in response to criticism. Conclusions. It is demonstrated that Quentin Skinner’s early methodology constitutes a coherent and consistent system of interpretive principles that had taken shape by 1972. His later works testify not to a radical change in approach, but rather to the development, clarification, and reasoned defense of the core assumptions of contextualism already formulated in his earlier writings.